A Physical Theory of the Finite Elastic-Viscoplastic Behaviour of Single Crystals - Teodosiu, C. (Engineering Transactions, 1975)
The aim of this paper is to review some of the main results concerning the mycrodynamics of dislocation motion in single crystals and to construct a finite phenomenological theory of the elastic-plastic behaviour on the basis of these results. The physical research done in the last forty years has shown that plasticity and viscoplasticity are typical properties of crystalline materials and that the motion of crystal defects (dislocations, point defects, grain and phase boundaries) is the main elementary process that is macroscopically observed as viscoplastic deformation. However, the real physical microscopic process is so complex that any macroscopic theory, derived by applying certain averaging procedures, has to focus on merely the main aspects of the process, in the hope- of clarifying their relative importance in various regimes of loading, temperature, and crystal conditions. This paper is intended to give a sufficient general description of the elastic-viscoplastic behaviour of single crystals. However, anelastic deformation, viscoelastic deformation produced by the motion of point defects, as well as recovery processes are not taken into account, and unloading is considered as purely elastic(1). The first three sections review the main present knowledge concerning the microdynamics of viscoplastic flow, in order to get some guidance for the macroscopic theory, which is developed in the last five sections of the paper, and which is based on previous work by KRÖNBR and TEODOSIU [4] and TEODOSIU [5].